Does wearing a prophylactic ankle brace during drop landings affect lower extremity kinematics and ground reaction - Simpson, K. J.; Yom, J. P.; Fu, Y. C.; Arnett, S. W.; O'Rourke, S.; Brown, C. N. (Journal of Applied Biomechanics, 2013)
The objective of the study was to determine if prophylactic ankle bracing worn by females during landings produces abnormal lower extremity mechanics. Angular kinematic and ground reaction force (GRF) data were obtained for 16 athletically experienced females who performed brace and no-brace drop landings. The brace condition displayed reduced in/external rotation and flexion displacements about the ankle and knee joints and increased vertical and mediolateral GRF peak magnitudes and rate of vertical GRF application (paired t test, P < .05). The ankle and knee joints landed in a less plantar flexed and more flexed position, respectively. No significant ab/adduction outcomes may have occurred due to interparticipant variability and/or a lack of brace restriction. During typical landings, this lace-up brace increases vertical GRF, decreases ankle and knee joint displacements of flexion and int/external rotation, but minimally affects ab/adduction displacements.